CHARACTERISTICS OF BONE MARROW MICROENVIRONMENT IN MULTIPLE MYELOMA BEFORE AND AFTER TREATMENT - V. I. Rugal; S. S. Bessmeltsev; N. Yu. Semenova; S. V. Gritsaev; I. I. Kostroma; N. I. Enukashvili; A. V. Chubar; D. A. Ivolgin (Сибирский научный медицинский журнал)
The purpose of the study is to evaluate the morphological and functional features of the tumor microenvironment and the cultural characteristics of mesenchymal stromal cells (MSC) of patients with multiple myeloma (MM) before and after treatment. Material and methods. Parenchymal and stromal bone marrow tissue in iliac bone trepanobiopsy of 32 patients with MM aged from 48 to 78 years (median age 56 years) before and after treatment was investigated. The study applied histological, immunohistochemical and cultural methods. Results and discussion. Сhanges of stromal microenvironment of bone marrow in all patients with MM have been revealed: increased microvascular density and the number of endosteal stromal cells, strengthening of reticulin fiber in subendosteal and perivascular spaces. Increased angiogenesis correlates with the number of plasma cells in the myelogram (r = 0.58; p < 0.05) and with the type of bone marrow infiltration (r = 0.85; р < 0.05), as well as with osteodestructive changes in the patient’s history (r = 0.65; p < 0.05). Significant changes in MSC cultures, both before and after therapy, including autologous hematopoietic stem-cell transplantation, were shown. Bone marrow MSC of patients with MM had decreased speed of proliferation (2.4 times on average), total time of passaging from 7 to 5 passages, increased expression of markers associated with myofibroblastic phenotype and aging (smooth muscle actin, β-galactosidase) compared to healthy donors. Conclusion. MSC cultures and BM niche forming elements of patients with MM have signs of tumor-associated microenvironment, despite the treatment of the underlying disease.